(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Cybersecurity is a fundamental concept in modern-day organizations. Firms are constantly exploring security solutions to keep them secure from security compromises that bear a great potential of disrupting their daily operations. The cybersecurity landscape is highly diverse and incorporates numerous elements that firms can exploit to protect vital corporate systems, including networks and sensitive resources such as data. Google is highly conscious of cybersecurity and employs every measure to protect its vital IT resources and systems from security threats. Google’s cybersecurity landscape is significantly mature and employs multiple plans that guarantee infrastructural security, data asset management, and effective access control. The firm’s security policies greatly prioritize promoting employee security awareness as the firm understands that workers form a fundamental component of its entire cybersecurity plan. This paper explores Google’s cybersecurity plan by focusing on cybersecurity security awareness programs, company information exposure on social networking sites, and the effects of not using encryption on network or Internet traffic. The paper will similarly recommend ways of minimizing information exposure while developing an understanding between password strengths and password managers in cybersecurity.